Safety and efficacy of fixed-dose combination of dapagliflozin and saxagliptin in patients with type 2 diabetes mellitus – a phase 4 study in India - Wangnoo, S. K.; Bhadada, Sanjay Kumar; Farishta, Faraz; Jayaram Naidu, Girithara Gopalakrishnan; Pattnaik, Indira; Manohar, K. N.; Singh, K. P.; Gupta, Sandeep Kumar; Bharath, H. S.; Ghosh, Sujoy (Frontiers in Endocrinology, 2025)
ObjectiveTo determine the post-marketing safety profile of a once-daily fixed-dose combination (FDC) of dapagliflozin (10 mg) and saxagliptin (5 mg) given orally for 24 weeks or until discontinuation, in Indian patients with type 2 diabetes mellitus (T2DM) who are on stable dose of metformin.DesignProspective, single-arm, multicenter studySettingAdult patients with T2DM enrolled from April 2021 to March 2023 across 9 study sites in IndiaOutcome measuresThe primary objective was to determine the adverse event (AE) profile of the FDC. Additionally, we assessed changes in glycated hemoglobin (HbA1c), fasting plasma glucose (FPG), systolic blood pressure, and body weight at 24 weeks, compared to baseline.ResultsOf the 196 patients (median age [range]: 53 [20 to 78] years) analyzed, 61.2% were males with mean ± standard deviation [SD] duration of T2DM of 7.1 ± 5.7 years. Overall, 111 (56.6%) presented with ≥1 comorbidity; the most frequent being hypertension (57; 29.1%). At 24 weeks, a total of 22 patients (11.2%) experienced 40 AEs; the majority of them had mild AEs. The most frequent AEs included urinary tract infection (5; 2.6%), pyrexia (5; 2.6%), nasopharyngitis (3; 1.5%), and balanoposthitis (3; 1.5%). The AEs of special interest reported were genital tract infection (3; 1.5%) and hypoglycemia (1; 0.5%). No serious AEs were reported. None of the AEs required treatment discontinuation. Three (1.5%) patients had AEs leading to temporary interruption of the study drug. No deaths were reported in this study. The mean absolute change in HbA1c (1.2% ± 1.1%), FPG (24.4 ± 62.9 mg/dL), and weight (2.1 ± 4.0 kg) from baseline to 24 weeks was statistically significant (p < 0.0001).ConclusionOur study demonstrated the safety and efficacy of once-daily FDC of dapagliflozin and saxagliptin when added to metformin in Indian patients with T2DM.